2019
DOI: 10.1371/journal.pone.0218511
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal contraceptive use and Staphylococcus aureus nasal and throat carriage in a Norwegian youth population

Abstract: Background Use of hormonal contraceptives has been associated with Staphylococcus aureus nasal carriage in adult women. However, the role of hormonal contraceptives in S . aureus colonization among adolescents and associations with progestin only contraceptives are unknown. Methods We obtained nasal and throat swab samples from 439 girls aged 17–21 years in the population-based Tromsø study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 33 publications
3
16
0
Order By: Relevance
“…From the population-based sixth Tromsø study (2007–2008), we reported higher nasal carriage among men and sex-differences in the distribution of S. aureus spa types (genetic variance by S. aureus protein A (spa) typing) ( 9 ). Among 400 young women in the Tromsø study fit futures (2012–2013), where 50% used hormonal contraception, we found a positive dose-response relationship between oestrogen dose and S. aureus nasal carriage, and a negative association between exogenous progesterone alone and nasal carriage ( 17 ). To our knowledge, no epidemiological study has examined whether endogenous sex-hormone levels are associated with S. aureus nasal carriage among women.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…From the population-based sixth Tromsø study (2007–2008), we reported higher nasal carriage among men and sex-differences in the distribution of S. aureus spa types (genetic variance by S. aureus protein A (spa) typing) ( 9 ). Among 400 young women in the Tromsø study fit futures (2012–2013), where 50% used hormonal contraception, we found a positive dose-response relationship between oestrogen dose and S. aureus nasal carriage, and a negative association between exogenous progesterone alone and nasal carriage ( 17 ). To our knowledge, no epidemiological study has examined whether endogenous sex-hormone levels are associated with S. aureus nasal carriage among women.…”
Section: Introductionmentioning
confidence: 87%
“…Smaller studies among women have found a positive association of nasal S. aureus carriage with biomarkers of endogenous oestrogen level ( 15 ), as well as of nasal S. aureus carriage with exogenous oestrogen and progesterone (i.e. hormonal contraceptive combination preparations) ( 16 , 17 ). One small study among premenopausal women found higher prevalence of persistent throat carriage of S. aureus with increasing levels of free fraction testosterone ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicate higher probability of nasal colonization in men which is a major risk factor for invasive S. aureus infections (37). Other studies show that circulating levels of testosterone and use of hormone contraceptives among females alter nasal colonization indicating that sex hormones affect the immune response to S. aureus (38,39). The substantially higher prevalence of S. aureus colonization in men is of particular interest, and preventive measures like eradication or temporary suppression could lower the risk of invasive infections (40), which is especially important in hospitalized patients.…”
Section: E T H I C Smentioning
confidence: 99%
“…Although Stensen et al reported that men have higher S . aureus nasal carrier rates than women [ 50 ], female sex was an independent risk factor for S . aureus colonization in the present study.…”
Section: Discussionmentioning
confidence: 99%